AN EFFICIENT MICROCONTROLLER COURSE WITH AN AFFORDABLE AND EASY TO USE DEVELOPMENT SETUP - YÜKSEKKAYA, Mehmet; HABERAL, O. Erdem (The Eurasia Proceedings of Educational and Social Sciences, 2015)
Microprocessors/Microcontrollers have been widely used in electronic products so they have been taught to electrical, computer and mechatronic engineering undergrads. Since medical electronics devices are also use microprocessors/microcontrollers, biomedical engineering undergrads should have knowledge and programming experience in microcontroller based systems. Due to this fact microprocessors/microcontrollers have been taught as a 5 hour/14 week lecture and laboratory course at the 5th semester in Başkent University Biomedical Engineering Program Ankara, Turkey. The main difficulties in microcontroller programing course for a multidisciplinary program such as biomedical engineering are insufficient allocation in the curriculum, shortage of lab space and budget constraints. Also the complexity of the development setups and spending too much time to understand the setup instead of experimenting it are problems for students and instructors. Students lose their attraction while spending time to effectively use of development tools. For this reason an efficient microcontroller course with its laboratory and a project work is developed which puts emphasis on learning the futures of microcontroller based system and applying many instrumentation designs. In order to increase the efficiency of the course an affordable, easy to use and modular development board with a free compiler for 2K program code and a free programmer software are used and important improvements are applied. Throughout the paper the details about the lectures, laboratories and development tools and their improvements are described. The methodology for active learning and syllabus design and determination of learning objectives are discussed. The efficiency of the course is tested by overall grades and responses of students. A remarkable success observed on the results.